ChemInform Abstract: General and Rapid Pyrimidine Condensation by Addressing the Rate Limiting Aromatization. Issue 48 (2nd December 2014) - Fandrick, Daniel R.; Reinhardt, Delia; Desrosiers, Jean‐Nicolas; Sanyal, Sanjit; Fandrick, Keith R.; Ma, Shengli; Grinberg, Nelu; Lee, Heewon; Song, Jinhua J.; Senanayake, Chris H.
Abstract The amidines are used in form of their hydrochlorides.